(3GdeQGLYI hJObjb GdMSGHGJ (B:s (3GdEWGQ GdfXQj hGdeeGQSI GdJWHjbjI (B/s - (3GdJgGej, WhGgQ eMeOs; (3UOjbj, eSYhOs ((3GdLRGFQ (B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2005)
(3eGgjI GdeQGLYI(B- (3eYGjjQ GdeQGLYI(B- (3GdeHGOF GdeMGSHjI(B- (3fXGe GdQbGHI GdOGNdjI(B- (3ebheGJ fXGe GdQbGHI GdOGNdjI(B- (3ELQGAGJ fXGe GdQbGHI GdOGNdjI(B- (3GdELQGAGJ GdYedjI ddeQGLYI(B- (3Jbjje fXGe GdQbGHI GdOGNdjI(B- (3OQGSI GdMGdI(B.s
(3GdeQGLY U(B.193s
Keywords: (3GdeQGLYIs; (3GdfXGe GdeMGSHjs; (3JObjb GdMSGHGJs